The Mona Lisa Illusion—Scientists See Her Looking at Them Though She Isn't. (January 2019) - Horstmann, Gernot; Loth, Sebastian
If the person depicted in an image gazes at the camera or painter, a viewer perceives this as being gazed at. The viewers' perception holds irrespectively of their position relative to image. This is the Mona Lisa effect named after the subject of Leonardo's famous painting La Gioconda . The effect occurs reliably but was not tested with Mona Lisa herself. Remarkably, viewers judged Mona Lisa's gaze as directed to their right-hand side irrespectively of the image zoom, its horizontal position on screen, and the distance of the ruler that was used for measuring the gaze direction.